Effect of Coffee Ages and Shade Types on Soil Moisture and Soil N, P, K Availability in UB Forest - zenny faridatus sa'diyah; Sugeng Prijono; Retno Suntari; Zaenal Kusuma (JOURNAL OF TROPICAL SOILS, 2023)
Water and nutrients is important for plant which has its characteristics. This study has been carried out in the UB (Brawijaya University) forest about soil moisture content during rainy and dry seasons, Total-N, -P, -K from litter on different types of shade and age of coffee plants, and their effect on soil Available-N, -P, and -K. There are P1 (control), P2 (4-year-coffee + pine), P3 (7-year-coffee + pine), P4 (4-year-coffee + mahogany), and P5 (7-year-coffee + mahogany). These treatments affected to total soil moisture storage, Total-N, -P, -K of litter, and Available-N, -P, -K in the soil. The soil moisture storage change between rainy and dry seasons was 36.97 mm. The highest Total-N, -P, and -K of litter was 11.00 kg ha-1 y-1 at P3, 1.06 kg ha-1 y-1 at P2, and 4.35 kg ha-1 y-1 at P3, which was inconsistently associated with high soil nutrients. The highest Total-N was 0.40 (0-20 cm), 0.27 (20-40 cm), 0.30% (40-60 cm) at P4, Available-K was 1.69 (0-20 cm), 1.64 (20-40 cm), 1.87 cmol kg-1 (40-60 cm) at P5, and Available-P was 15.21 (0-20 cm), 14.06 (20-40 cm), 12.64 mg kg-1 (40-60 cm) at P1.